2020
DOI: 10.1111/1751-7915.13688
|View full text |Cite
|
Sign up to set email alerts
|

We and herbivores eat endophytes

Abstract: Here a cycle of endophytic‐enteric‐soil‐endophytic microbes is proposed which has relevance for health and comprises the fate of animal faeces as natural microbial inoculants for plants that constitute bacterial sources for animal guts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 192 publications
0
17
0
Order By: Relevance
“…Transiting through the gut of herbivores and omnivores is part of the lifecycle of such nomadic bacteria. 15 Lactiplantibacillus plantarum (formerly known as Lactobacillus plantarum ) and Pediococcus acidilactici are two such species of lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Transiting through the gut of herbivores and omnivores is part of the lifecycle of such nomadic bacteria. 15 Lactiplantibacillus plantarum (formerly known as Lactobacillus plantarum ) and Pediococcus acidilactici are two such species of lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genera such as Unclassified_o_Pleosporales, Erythrobasidium and Trimmatostroma are abundant in the faeces and expand with the development of pandas, and most of these fungi in the intestines are pathogenic of plant origin [ 35 , 36 ], but interestingly, the fungal flora structure in the intestines of giant pandas has always been relatively uniform. Martinez-Romero et al have also found that the plant endophytes could form a stably and functionally microbial structure during long-term interaction with herbivorous animals [ 37 , 38 ]. There were no obviously predominant genera to colonize the intestines of giant pandas for a long time, which might be also a self-protection mechanism of the host for defending the conditional pathogenic microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…As an herbivore, the volcano rabbit would feed on plants that contain endophytes which may become part of the gut microbiota. This occurs in other herbivorous animals' endophytes that have tannases and enzymes to degrade plant cell wall components (Martinez-Romero et al, 2021). A critical issue that should be considered is whether the microbiota identified from herbivorous animals represent bona fide gut bacteria or reflect endophytes that are still contained within the plant tissue fragments macerated during DNA extraction.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Fecal ingestion would allow a second digestion of plant fibers, a process that could be considered analogous to ruminant digestion. Coprophagy is as well a very efficient way to recycle gut microbiota (Martinez-Romero et al, 2021). In most lagomorph studies, Firmicutes were found as the most abundant bacteria (North, Zotte & Hoffman, 2019;Stalder et al, 2019;Velasco-Galilea et al, 2018) followed by Bacteroidetes (North, Zotte & Hoffman, 2019;Stalder et al, 2019), although Crowley et al (2017) found that both Bacteroides and Firmicutes were equally abundant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation